Auditoría operativa al área de talento humano y su relación con la optimización de los servicios del grupo de fuerzas especiales Nº 26 CENEPA, año 2013 - Villarroel Villarroel, Argelis Adriana (2015)
This research was conducted at the Department of Human Talent Group Forces Special Nº 26 CENEPA., Domiciled in the city of Quevedo, Los Rios Province, which has been operating since 1966, with the aim of contributing to the management operation of the institution, is if they meet the objectives of efficient, effective and economic way, the next target was raised: "To determine the incidence of an operational audit to the area of human talent in optimizing services Group Forces Special Nº 26 CENEPA, 2013 ", whose diagnosis has allowed now identify the unit has shortcomings in the Human Resource Department, they will not let you effectively develop activities, because it is not properly applied Internal Controls in this area. Therefore he was born the need for an operational audit to analyze the functions of the staff, and; the procedures to be followed, to route all the activities taking place in the institution and thus improve the operational management. Evaluation of Internal Control in the Department of Human Talent Group Forces Special Nº 26 CENEPA, reflects us that policies do not apply in the department efficiently through ignorance, present in the operational area a confidence level of 93 % and the risk level of 7% is low. It was therefore proposed labor a report of internal control, with the respective findings to present conclusions and alternative solutions by recommendations of which must be analyzed and reviewed by the directors of the Group Forces Special Nº 26 CENEPA, and thus the can put into practice for the benefit of the institution.